Characterization of basic nitrogen compounds isolated with FeCl3 in vacuum gas oil and its hydrotreated product. (15th February 2020) - Lai, Tingting; Mao, Yichao; Wang, Wei; Wang, Xieqing; Wang, Naixin; Liu, Zelong
Highlights: Basic nitrogen compounds were isolated from vacuum gas oils with FeCl3 . The isolated basic nitrogen compounds were characterized by FT-ICR MS. GC × GC-TOFMS of basic nitrogen compounds were reported. The transformation of basic nitrogen compounds during hydrotreating was revealed. Abstract: The basic nitrogen compounds in petroleum are harmful heteroaromatic compounds, which would substantially affect the refining process and the quality of the resultant products. Obtaining comprehensive molecular information of the basic nitrogen compounds is challenging, particularly for those in heavy oils. In this work, a novel separation method was developed to isolate the basic nitrogen compounds from vacuum gas oil and its hydrotreated product with high recovery and high purity. The basic nitrogen compounds were isolated from the vacuum gas oil and its hydrotreated product by the formation of complexes coordinated with FeCl3 . Then, the insoluble complexes were treated by NaOH to destroy the coordinate bonds between the FeCl3 and basic nitrogen compounds. The separated basic nitrogen compounds were characterized by Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) and comprehensive two-dimensional (2D) gas chromatography coupled with high resolution time of flight mass spectrometry (GC × GC-TOFMS). The separated basic nitrogen compounds facilitated the GC × GC-TOFMS analysis due to the reduced matrix complexity. The basic nitrogen compounds from vacuum gas oil are mainly tricyclic and tetracyclic nitrogen-containing aromatic compounds, such as benzoquinolines and benzacridines. The basic nitrogen compounds from the vacuum gas oil with short alkyl chains can be preferentially removed by hydrotreatment. Moreover, partially saturated products of the basic nitrogen compounds were widely found in the hydrotreated vacuum gas oil, such as tetrahydrobenzoquinolines, octahydrobenzoquinolines, tetrahydroindenoquinolines, and octahydroindenoquinolines. This study contributes to the structural characterization of basic nitrogen compounds in heavy oils and the conversion of these compounds during hydrotreating.